2021
DOI: 10.1021/acsaem.1c02812
|View full text |Cite
|
Sign up to set email alerts
|

A Synergy Effect of Coadditives for Vertical Orientation of Two-Dimensional Perovskite Solar Cells Based on Butylammonium Iodide with Improved Efficiency

Abstract: Two-dimensional (2D) perovskites show better resistance and optoelectronic characteristics than three-dimensional compounds. However, the high exciton energy and insufficient interfacial charge flow significantly reduce perovskite device performance. In this regard, a strategy to obtain high-performance 2D perovskite solar cells employing synergistic impact of coadditives (NH4SCN and HCl) to enable the proper alignment of perovskite films through the substrate, which eventually increases crystallinity and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…The longer PL lifetime of the perovskite film with MACl suggests reduced non-radiative recombination and a lower trap density. 38 The SCLC measurements were conducted to explore the effects of the additive MACl on the trap states and carrier dynamics of quasi-2D perovskite films. The carrier mobilities and trap densities of devices with and without MACl were also calculated based on the V TFL and Mott-Gurney's law with the SCLC curves in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer PL lifetime of the perovskite film with MACl suggests reduced non-radiative recombination and a lower trap density. 38 The SCLC measurements were conducted to explore the effects of the additive MACl on the trap states and carrier dynamics of quasi-2D perovskite films. The carrier mobilities and trap densities of devices with and without MACl were also calculated based on the V TFL and Mott-Gurney's law with the SCLC curves in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The longer PL lifetime of the perovskite film with MACl suggests reduced non-radiative recombination and a lower trap density. 38…”
Section: Resultsmentioning
confidence: 99%
“…[36] Apart from these studies, many groups have reported different processing techniques that can enhance vertical orientation, although they seldom report the underlying mechanism. Among these techniques are hot casting, [37] spin coating with antisolvent, [34,38] use of co-solvents, [39] and use of pressure and heat. [40]…”
Section: Crystal Orientationmentioning
confidence: 99%
“…Recently, the use of NH 4 SCN and HCl as co‐additives led to an improvement of optoelectronic properties of (BA) 2 (FAMA) 3 Pb 4 I 13 that resulted in a PCE of 16.45%. [ 38 ] Pb(SCN) 2 has also shown promise in enhancing film morphology and charge carrier mobility while reducing non‐radiative recombination. The use of this additive has been reported to push the PCE of a solar cell based on propargylamine spacer to 15.20%, whereas the pristine film stopped at 12.15%.…”
Section: Molecular and Additive Engineeringmentioning
confidence: 99%
“…Additional treatment can also be applied in the preparation of 2D DJ phases to improve further their film quality (anti-solvent treatment, additive, etc.). [47,48] Furthermore, the DJ structure has a substantially higher binding energy across the stacked structures as well as a much higher molecular dissociation energy than the RP structure. [49] In this article, we present first the overview of crystal structure and optoelectronic characteristics of low dimensions.…”
mentioning
confidence: 99%